2021
DOI: 10.24867/jged-2021-4-005
|View full text |Cite
|
Sign up to set email alerts
|

Use and analysis of UV varnish printed braille information on commercial packaging products

Abstract: This paper investigates the possibility of reproducing Braille by UV ink-jet printing on self-adhesive labels, previously printed by flexo printing technol- ogy. The aim was to determine whether it is possible to reproduce Braille, the degree of quality of created Braille dots (cells), the legibility of Braille text, and how many layers of varnish are necessary for quality reproduc- tion. The Braille letter was applied to the previously printed label (design) using 8, 10, 12, 14 and 16 layers of varnish. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The printing was done from 1 to 12 layers, so colour difference could be monitored with every additional layer of varnish. Final 12 layers of varnish were applied, since previous research showed that with this number of layers of UV varnish legible Braille is obtained (Miloš, Vujčić & Majnarić, 2021). Gloss mode (drying with one UV lamp) was used for printing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The printing was done from 1 to 12 layers, so colour difference could be monitored with every additional layer of varnish. Final 12 layers of varnish were applied, since previous research showed that with this number of layers of UV varnish legible Braille is obtained (Miloš, Vujčić & Majnarić, 2021). Gloss mode (drying with one UV lamp) was used for printing.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, UV varnish is also used for printing braille letters, and also illustrations in braille books, signage and labeling in galleries and museums, etc. (Vujčić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%